Charlie’S Depression in The Perks of being a Wallflower - Farah Kamilia (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2021)
This study was made to discuss the depression experienced by the main character in the novel The Perks of Being a Wallflower, Charlie. Psychoanalysis by Jacques Lacan is a theory that will be used in analyzing this study. The focus of this study is the depression experienced by Charlie due to events in his past that are quite traumatic and greatly influence Charlie's personal and social life. This study aims to find out the factors that can cause depression in Charlie. This study was conducted by analyzing Charlie's situation from the beginning using the Psychoanalysis theory developed by Jacques Lacan. The analysis shows that family behavior and the school environment make shy Charlie a teenage figure who always feels unacceptable and unloved. In this analysis, Jacques Lacan proves in the psychoanalytic theory that he developed, that the outside world contributes a large influence on each stage of a person's life in shaping who he is and how he behaves. Can also be found here in the results of this analysis, if the influence of the outside world on an individual is also able to affect one's mentality.